Perlindungan Data Pribadi di Indonesia Pasca Pengesahan UU No. 27 Tahun 2022 di Era Digital - Yurike Maulina (As-Shahifah : Journal of Constitutional Law and Governance, 2025)
The rapid development of information technology and the enormous potential of the digital economy have had positive impacts, but have also given rise to new challenges, particularly regarding the protection of the right to privacy and personal data. Privacy is a fundamental right that, while not absolute, still requires strong legal protection, especially in today's digital era, which is rife with online activity. The enactment of Law Number 27 of 2022 concerning Personal Data Protection is a crucial step in providing legal certainty for the public, particularly consumers conducting online transactions. This law unifies various sectoral regulations into a single, comprehensive and consistent legal framework, aligning with global data protection principles. This research uses a normative legal method that examines applicable laws and regulations. Law Number 27 of 2022 introduces a modern approach to personal data protection, which aligns with the European Union's General Data Protection Regulation (GDPR). It regulates data controllers, data processors, and the rights of data subjects. One of the advantages of this law is its broad scope, encompassing the personal data of both Indonesian citizens and foreign nationals, both within and outside Indonesian jurisdiction, as stated in Article 2 paragraph (1). This demonstrates Indonesia's commitment to protecting personal data in accordance with global standards. With the enactment of this law, the public now has a stronger legal basis for demanding their rights to personal data and encourages accountability among electronic system administrators.